2017
DOI: 10.1063/1.4984995
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental characterization of a plasma induced on a solid target by an intense pulsed multi-MeV e-beam

Abstract: We investigate the interaction of an intense pulsed multi MeV electron beam with a solid target on the ASTERIX high voltage generator using a set of numerical and experimental tools. Physical mechanisms occurring at various stages are examined, from electron beam dynamics to X-ray production, including plasma generation at the solid target surface. First, the electron beam characteristics are determined using 2D axisymmetric Particle-In-Cell calculations and a good agreement is found between calculated and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For this calculation, the expansion velocity v expan is set to 150 km/s and r 0 ¼ 100 S/m. Equation (6) shows that the expansion velocity is an important parameter of the model. To determine it, we first analyze the measured signals, which show that a transmission minimum is systematically observed at the end of the ESD, i.e., at the average values of 620 and 750 ns after the beginning of the phenomena, respectively, PE and PTFE.…”
Section: B Plasma Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…For this calculation, the expansion velocity v expan is set to 150 km/s and r 0 ¼ 100 S/m. Equation (6) shows that the expansion velocity is an important parameter of the model. To determine it, we first analyze the measured signals, which show that a transmission minimum is systematically observed at the end of the ESD, i.e., at the average values of 620 and 750 ns after the beginning of the phenomena, respectively, PE and PTFE.…”
Section: B Plasma Modelingmentioning
confidence: 99%
“…In the case of the ablation plasma, it has been shown that a low ionized plasma surrounds this hot core and is about twice as large as the size of the inner core. 6,[36][37][38][39] So, the magnitudes of the expansion velocities determined from the optical imagery may underestimate the expansion velocity of the low ionized region of the plasma.…”
Section: B Plasma Modelingmentioning
confidence: 99%
See 1 more Smart Citation